The Republic and the Kingdom: A Filipino postmodern reflection on Thailand as a parallel other - Contreras, Antonio P. (Animo Repository, 2008)
The position of the other in identity politics is a defining place for subject formation for it serves as a space not only to delineate what one is not, but also where one differs. This paper inquires into the political implications to Filipino identity formation of looking at Thailand as a "parallel other." In this context, such form of otherness is considered not as a subordinated alterity, but as a template upon which one can locate a meaning that would otherwise be dismissed as incoherent or unrecognizable. It is through the lens of the Thai experience that the paper locates the formation of Filipino identity, not as an inferior position, but just as a different modality for finding social meaning. It is through this that the paper shows the possibility of locating in the Thai template a canvas upon which the Filipino political experience can be drawn and mapped.